O Congresso Nacional: alternativas de representação politica e paradigmas eleitorais - Amador, Luis Filipe Chateaubriand Baracho Ferreirinha (1996)
This project intends to analyze the operation structure of the Brazilian Electoral System, wich, as I here attempt to explain, does not appreciate political parties as appropriate means of interaction between Society and State. As a direct result, there are in Brazil many political parties actively inoperative and representatively weak. It is a basic theory of this project the fact that some political groups take advantage of pratices that are noxious to the participatory democracy using the electoral system. Therefore, the response drawn from the votes is different than its political representation. The National House of Representatives, subject of greatest distortions, is the starting point of this project. From that center of political power, we can observe and analyze the effective institucional engineering and its way of reproduction to the different spheres of power. The methodology used in this project is separated in two different parts: . In the theoretical part (chapters II and III), I try to comparatively analyze the passive propositions (of each item) of adoption, and also explain my opinion about them. . In the practical part (chapter IV), I explain a proposition of agenda to reform the electoral system, consistent with that previously analyzed.